Cadmium Tolerance and Bioremediation Potential of Bacteria Isolated from Soils Irrigated with Untreated Industrial Effluent: Cadmium Tolerant Bacterial Isolation - Ahmad, Rizwan; Hassan, Muhammad Mahmood-ul-; Yasin, Muhammad; Suthor, Vishandas (Biological Sciences - PJSIR, 2015)
The present study was aimed to investigate the Cd tolerance of bacteria isolated from municipal effluent irrigated soils. Thirty bacterial strains were isolated and screened for their Cd+ tolerance by growing on nutrient agar plates amended with varying amount of Cd+. Out of them four bacteria (GS2, GS5, GS10 and GS20) were found highly Cd tolerant (600 ppm Cd). The minimum inhibitory concentration of Cd+ was found 200 ppm. The isolates showed optimum growth at 30 °C and pH 7.5-8.5. Growth curve study against different concentrations of Cd (0-600 ppm) revealed that GS2 was more tolerant among selected strains showing only 33% reduction in growth compared to 64% by GS5 and 77% by both GS10 and GS20 at 600 ppm Cd. Inoculation of maize seeds with Cd tolerant bacteria for root elongation demonstrated up to 1.7 fold increase in root elongation (in the absence of Cd) and up to 1.5 fold (in the presence of 50 ppm Cd) compared to the un-inoculated plants. The results of the study revealed that the bacterial isolates exhibiting great Cd tolerance and growth promoting activity can be potential candidates for bioremediation of metal contaminated soils and wastewaters.